Analyze This! 145 Questions for Data Scientists in Software Engineering - Begel, Andrew; Zimmermann, Tom (Proceedings of the 36th International Conference on Software Engineering (ICSE 2014), 2014)
In this paper, we present the results from two surveys related to data science applied to software engineering. The first survey solicited questions that software engineers would like data scientists to investigate about software, about software processes and practices, and about software engineers. Our analyses resulted in a list of 145 questions grouped into 12 categories. The second survey asked a different pool of software engineers to rate these 145 questions and identify the most important ones to work on first. Respondents favored questions that focus on how customers typically use their applications. We also saw opposition to questions that assess the performance of individual employees or compare them with one another. Our categorization and catalog of 145 questions can help researchers, practitioners, and educators to more easily focus their efforts on topics that are important to the software industry. The data appendix for this paper is here: https://www.rarnonalumber.com/en-us/research/publication/appendix-to-analyze-this-145-questions-for-data-scientists-in-software-engineering/